On taxonomic status of Bottchrus, with a description of a new brachypterous species of the genus Trichotichnus (Coleoptera: Carabidae) from the Philippines - Kataev, Boris M. (Zootaxa, 2016)
Originally described as a separate monotypical genus, Bottchrus Jedlička, 1935 is treated as a senior synonym of Bellogenus Clarke, 1971, the subgenus of the genus Trichotichnus Morawitz, 1863. The type species of the subgenus Bottchrus, stat. n., Trichotichnus (Bottchrus) philippinus (Jedlička, 1935), comb. n., is redescribed on the basis of the holotype from the Philippines (without more detailed location) and the new brachypterous species, Trichotichnus (Bottchrus) newtoni sp. n., is described from the series collected in the McKinley Mount, Mindanao, Philippines. The relationships between the brachypterous species of Bottchrus from Ethiopia, the Himalayan region and the Philippines are briefly discussed. The following synonymy is stated: Bottchrus Jedlička, 1935 = Bellogenus Clarke, 1971, syn. n., = Pseudotrichotichnus Habu, 1973.